2019
DOI: 10.1186/s12920-019-0601-9
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate causes the alterations of endoplasmic reticulum related mRNAs and lncRNAs in endometrial cancer cells

Abstract: BackgroundProgestin is effective to promote endometrial cancer (EC) cells apoptosis, however, continuous progestin administration causes low level of progestin receptor B (PRB), further resulting in progestin resistance. Here, we performed microarray analysis on Ishikawa cells (PRB+) treated with medroxyprogesterone acetate (MPA) to explore the molecular mechanism underlying the inhibitory influence of MPA on PRB+ EC cells.MethodsMicroarray analysis was performed by using Ishikawa cells (PRB+) treated with MPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…To further study HERP localization and expression in neurons after ICH, immunofluorescent staining was performed with cells specific marker: NeuN (a marker of neuron). As described previously ( Cao et al, 2019 ), we found that HERP co-located with neurons in the cytoplasm. As shown in Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To further study HERP localization and expression in neurons after ICH, immunofluorescent staining was performed with cells specific marker: NeuN (a marker of neuron). As described previously ( Cao et al, 2019 ), we found that HERP co-located with neurons in the cytoplasm. As shown in Fig.…”
Section: Resultssupporting
confidence: 88%
“…Homocysteine-induced endoplasmic reticulum protein (HERP), a 54 kD transmembrane protein, is an early stress response protein encoded by homocysteine-inducible and ER-stress-inducible, ubiquitin-like domain member 1 (Herpud1) gene. It is dramatically induced by ER stress in a variety of pathological conditions, including ICH ( Cao et al, 2019 ; George et al, 2018 ; Kokame et al, 2000 ; Maeda et al, 2018 ). HERP also plays a significant role in ER-associated protein degradation (ERAD), which is the principal mechanism of protein degradation that misfolding unfortunately.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of studies have demonstrated that dysregulated lncRNAs play an important role in the carcinogenesis, development and metastasis of different types of tumor (33)(34)(35). A number of lncRNAs have been reported to be associated with the recurrence, metastasis and resistance to adjuvant therapy of patients with BC (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HOTAIR and LSD1 collaboratively repress PRB expression and thus reduce progesterone sensitivity in endometrial carcinoma cells 31 . CHOP and Lnc-CETP-3 might be involved in progesterone-PRB pathway to activate ER stress and provide therapeutic targets for EC patients with negative PRB expression 32 .…”
Section: Discussionmentioning
confidence: 99%